2019
DOI: 10.1039/c8tb02999g
|View full text |Cite
|
Sign up to set email alerts
|

Bionic cartilage acellular matrix microspheres as a scaffold for engineering cartilage

Abstract: Bionic cartilage acellular matrix microspheres (BCAMMs) made from decelluarized bionic cartilage microspheres (BCMs).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 57 publications
(60 reference statements)
0
5
0
Order By: Relevance
“…The cartilage particles were decellularized using the previously optimized decellularization procedure. 25 In brief, the cartilage particles were soaked in high and low osmotic pressure solution three times, and then alternately soaked in liquid nitrogen and 37 °C water bath for five rounds for 10 min each time. Subsequently, cell membranes were broken with 0.5% Triton X-100 solution, DNase I solution and DNA enzyme working solution were added to remove any remaining DNA.…”
Section: Materials and Mmethodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cartilage particles were decellularized using the previously optimized decellularization procedure. 25 In brief, the cartilage particles were soaked in high and low osmotic pressure solution three times, and then alternately soaked in liquid nitrogen and 37 °C water bath for five rounds for 10 min each time. Subsequently, cell membranes were broken with 0.5% Triton X-100 solution, DNase I solution and DNA enzyme working solution were added to remove any remaining DNA.…”
Section: Materials and Mmethodsmentioning
confidence: 99%
“…After drying, the cartilage was ground in a cryogenic grinder to obtain cartilage particles with the size of less than 100 μm. The cartilage particles were decellularized using the previously optimized decellularization procedure . In brief, the cartilage particles were soaked in high and low osmotic pressure solution three times, and then alternately soaked in liquid nitrogen and 37 °C water bath for five rounds for 10 min each time.…”
Section: Materials and Mmethodsmentioning
confidence: 99%
“…And the in vivo results demonstrated that these microspheres could compensate for the inductive lack of polymers and facilitate osteochondral differentiation. Furthermore, Liu et al prepared bionic cartilage ECM microspheres derived from MSCs and demonstrated their remarkable efficacy in promoting chondrogenesis without the need for any additional serum or induction components [57].…”
Section: Composite Microspheresmentioning
confidence: 99%
“…Cartilage tissue injury is one of the common but not self-healable diseases in clinical orthopedics. Artificial cartilage scaffolds have excellent mechanical and biological performance toward mimetic tissue environments and greatly relieve the patients’ physical and psychological distress. To date, approaches to transplantation of these scaffolds have been widely applied as ideal replacements for traditional therapies for cartilage tissue regeneration and repair. Material matrices are indispensable parts in this field and play critical roles in realizing these properties. , Typically, porous, water-rich hydrogels are able to mimic extracellular matrices and provide similar microenvironments for cell proliferation, nutrition delivery, and tissue generation. The introduction of functional components in hydrogels will improve their mechanical property, biocompatibility, diagnosis, and therapy performances.…”
Section: Introductionmentioning
confidence: 99%